When x = -1 and y = 2 > what is the value of the expression 2x^3 - 3xy?
First: replace "-1" with the x-variable and "2" with the y-variable...
2(-1)^3 - 3(-1)(2)
Sec: use PEMDAS > ( ), exponents, multiplication, division, addition & subtraction...
2(-1)(-1)(-1) - 3(-1)(2)
2(-1)(1) - 3(-1)(2)
2(-1) - 3(-1)(2)
- 2 - 3(-2)
- 2 + 6
= 4
2007-01-26 14:48:54
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
4
2007-01-26 13:15:03
·
answer #2
·
answered by jdog33 4
·
0⤊
0⤋
Note: -1 multiplied by itself 3 times gives you -1
Place your values into the expression:
2(-1)^3 - 3(-1)(2)
= -2-(-6)
=-2+6
=4
2007-01-26 13:17:32
·
answer #3
·
answered by Newman 4
·
0⤊
0⤋
2(-1)³ - 3(-1)(2) = 2(-1) - 3(-2) = -2 + 6 = 4
><
2007-01-26 13:24:54
·
answer #4
·
answered by aeiou 7
·
0⤊
0⤋
x = -1 and y= 2
Then,
2x^3 - 3xy = 2*-1^3-3*-1*2
=2*-1-3*-2
= -2+6
=4
2007-01-26 14:59:58
·
answer #5
·
answered by loally 2
·
0⤊
0⤋
2(-1)^3 - 3(-1)(2)
=2(-1) - (-6)
=6 - 2
=4
2007-01-26 13:14:58
·
answer #6
·
answered by Anonymous
·
2⤊
1⤋
2*(-1)^3-3*(-1)*2=
2*(-1)-3*(-1)*2=
(-2)-3*(-1)*2=
(-2)-(-3)*2=
(-2)-(-6)=4
~~~~~~~~~~4~~~~~~~~~~
Take it from somebody, who has a
102, in Mathematics Class!!!!!
2007-01-26 13:29:39
·
answer #7
·
answered by babodite 3
·
0⤊
0⤋
2*-1^3-3*-1*2
2*-1-3*-1*2
-2+6
4=answer
2007-01-27 01:16:55
·
answer #8
·
answered by 97979546546546546546546546546546 1
·
0⤊
0⤋